TO THE METHODOLOGY OF MONITORING OF EXPOSITIONAL -EXPERIMENTAL MEADOW STEPPESCREATED BY THE METHOD OF TURF PLANTING - E. V. Peshchanskaya; N. G. Likhovid (Наука. Инновации. Технологии, 2022)
Introduction. The article describes the prerequisites and stages of restoration of meadow steppes on the territory of the Stavropol Botanical Garden, created by planting sod, taken in natural conditions - mount Strizhament, mount Buchinka, Novomaryevskaya Polyana and Vishnevaya Polyana. The course of work is described, it was found that the best planting dates are spring and autumn, the average size of the turf is 27.9 × 23.5 cm2. The main part. The monitoring methodology developed in the course of research includes: the study of the influence of the maintenance regime on the species composition of the phytocenosis (mowed, reserved), the general characteristics of the phytocenosis (description of the course of seasonal changes, accounting for species saturation, accounting for productivity, morphometric studies of individual species, monitoring of the state of the dominant steppe formation, accounting for life forms, accounting for succession processes occurring in various variants, mapping sites, age composition of the population, phenological observations, studying the seed productivity of cenosis species, animal activity, etc.), study of rare species (population-quantitative records, age structure, ability of the population to self-support due to seed or vegetative reproduction, accounting for fruiting), study of underground parts of plants of phytocenosis. Recommended maintenance works are described (removal of vegetation that is not typical for the restored type of cenosis, protection of sites during periods of increased fire risk, contour mowing of adjacent territories to avoid fire spread, mowing, collecting and exporting hay from the territories of restored mowed areas, removal of tree and shrub growth on age-protected areas during their spontaneous afforestation). Results of reasearch. The current state of the exhibition and experimental plots is presented - high species saturation (74 ... 111 species) with a predominance of perennials - 82 ... 92%, the percentage of botanical groups in herbage - mixed herbs - 60 ... 69%, legumes - 9 ... 18%, cereals and sedges 18 ... 22%, the productivity of the grass - 23,0... 37.6 с/ha. In the areas of meadow-steppe formations, a total of 18 rare and endangered species are preserved. Under a permanent reservation conditions, microgroupings of the thickets of bushes type from Chamaecytisus ruthenicus, Genista tinctoria, Calamagrostis epigejos, species of the genus Rosa. Self-seeding of tree and shrub species are note with varying degrees of abundance.